Preparation method and application of Ru-based hydroxide electrocatalyst with high oxidation resistance

By introducing a hetero-support of titanium oxide in Ru-based catalysts, the electronic environment of Ru-based catalysts is adjusted using the "combination reaction-critical growth-in-in-situ nucleation-high temperature reduction" mechanism, the problem of unsatisfactory HOR performance and prone to oxidation and inactivation in the alkaline electrolytes is solved, and a high activity, stability and low-cost catalyst is achieved.

CN119581589APending Publication Date: 2025-03-07CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411562132.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing Ru-based catalysts have poor HOR performance in alkaline electrolytes and are prone to oxidation and inactivation under high anode potential, resulting in insufficient activity and poor stability.

Method used

The electrocatalyst supported by the titanium oxide hetero-supported Ru clusters was grown through the "combination reaction-critical growth-in-situ nucleation-high temperature reduction" mechanism, which regulates the electronic environment of Ru, changes the adsorption method of OHad and Had, and improves the activity and antioxidant ability of the catalyst.

Benefits of technology

The high HOR activity, antioxidant inactivation and stability of Ru-based catalysts in alkaline electrolytes are achieved, the cost of the catalyst is reduced, and the cost-effective Pt-free electrocatalyst is provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581589A_ABST
    Figure CN119581589A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Ru-based catalyst with excellent hydrogen oxidation catalytic activity and oxidation resistance, and aims to solve the problem that an alkaline fuel cell anode Ru-based catalyst is easy to inactivate and low in activity under high anode potential. The preparation method comprises the following steps: preparing a titanium oxide carrier from a titanium precursor solution through hydrothermal synthesis and high-temperature calcination, preparing a heterogeneous carrier through temperature programmed ammonification, and introducing Ru clusters on the surface of the carrier through Ru in-situ nucleation to obtain the Ru-coated TiON catalyst. The preparation method has the following advantages: the prepared Ru-based catalyst has independent double active sites, so that competitive adsorption of OHad and Had species is avoided; the prepared TiON carrier and Ru clusters have an electron dynamic circulation effect, so that the electronic structure property of Ru is remarkably influenced, the catalytic activity is improved, and the oxidation resistance is remarkably enhanced. Based on the characteristics, the prepared catalyst has excellent electrocatalytic activity and oxidation resistance at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrochemical technology, and in particular to a preparation method and application of a Ru-based hydrogen oxidation electrocatalyst with high antioxidant capacity. Background Art

[0002] As a clean and efficient energy carrier, hydrogen energy is gradually becoming an important pillar for countries to achieve energy transformation and environmental governance goals. Among them, hydrogen fuel cells are an effective power generation device that relies on hydrogen to obtain green electricity.

[0003] So far, most of the research and application of fuel cells have focused on proton exchange membrane fuel cells (PEMFCs) with high power density. PEMFCs convert chemical energy directly into electrical energy through hydrogen oxidation reaction (HOR) and oxygen reduction reaction (ORR) on the anode and cathode sides, respectively, where electrocatalysts are required to achieve satisfactory kinetics. However, the cathode and cathode reactions of PEMFCs under acidic electrolytes rely heavily on Pt-based electrocatalysts, acid-resistant stack hardware, and perfluorinated membranes, resulting in high costs, which severely limits the commercial development of fuel cells. Fortunately, anion exchange membrane fuel cells (AEMFCs) are considered as potential alternatives to PEMFCs in the field of hydrogen energy utilization due to the development of non-precious metal catalysts in ORR. However, the anode HOR process of AEMFCs still relies heavily on Pt-based catalysts. More importantly, the HOR kinetics under alkaline electrolytes, even with Pt / C catalysts, are several orders of magnitude slower than those under acidic electrolytes, resulting in much higher Pt loading in AEMFC systems. The resulting high-loaded anode Pt-based catalysts largely offset the cost advantage brought by the absence of precious metal cathodes. Therefore, it is highly desirable to develop cost-effective Pt-free electrocatalysts with high HOR activity, stability, and low cost in alkaline electrolytes.

[0004] Ruthenium (Ru) is a particularly promising alternative to Pt catalysts due to its low price (6%-36% of Pt), similar hydrogen binding energy (HBE) to Pt, highly adjustable electronic structure and high water dissociation efficiency. However, Ru has low intrinsic activity and lacks effective OH adsorption sites, which results in its HOR performance being still unsatisfactory. In addition, Ru-based catalysts deactivate rapidly at high anode potentials. The Ru-based catalysts reported so far mainly include RuMo / C[ACS SustainableChem.Eng.2022,10:1616.], RuNi / C[Nat.Commun.2020,11:5651.], Ru / C[Adv.EnergyMater.2023,13:2300881.], etc., which only solve the problem of insufficient Ru activity, but the problem of easy oxidative deactivation at high anode potentials has not been solved. Therefore, there are still major challenges in improving the intrinsic activity and anti-oxidative deactivation of HOR.

[0005] By introducing oxygen-philic titanium oxide, it will compete with Ru for the adsorption of OH ad , thereby reducing OH ad Excessive adsorption on Ru sites can avoid Ru deactivation. However, metal oxides have poor conductivity and small specific surface area, which seriously limits their performance. The introduction of titanium nitride can solve the shortcomings of insufficient conductivity and poor activity of titanium oxide. Therefore, the titanium oxynitride carrier obtained by in-situ growth takes into account the advantages of both oxides and nitrides, and modifies and adjusts Ru through the interface electronic effect, thereby solving its activity and deactivation problems. Summary of the invention

[0006] In view of the high cost of existing commercial catalysts and the shortcomings of Ru-based catalysts, the present invention provides a method for preparing and applying a Ru-based catalyst for an alkaline fuel cell anode with good antioxidant ability. The electrocatalyst of Ru clusters loaded on a titanium oxynitride heterogeneous carrier is in situ grown through the "chemical reaction-critical growth-in situ nucleation-high temperature reduction" mechanism, while taking into account the advantages of both oxides and nitrides. The resulting catalyst has ultra-high mass activity, antioxidant deactivation and stability for hydrogen oxidation reaction (HOR).

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] A method for preparing an alkaline fuel cell anode Ru-based catalyst with good antioxidant capacity comprises the following steps:

[0009] S1. Titanate nanofibers were prepared by alkali-assisted hydrothermal method. P25 was used as a titanium source and added to an alkaline solution of a certain concentration. The solution was ultrasonically stirred for a period of time, and the mixed solution was added to a Teflon container for hydrothermal reaction to obtain a precipitate.

[0010] S2. The precipitate of S1 is centrifugally washed until it becomes neutral, added into an acid solution of a certain concentration and allowed to stand for a period of time, and then filtered and dried to obtain titanate nanofibers.

[0011] S3. The titanate nanofibers are transferred to a muffle furnace for high-temperature calcination to obtain nano-TiO2 rods.

[0012] S4. A certain amount of nano-TiO2 rods are transferred to a tubular furnace, and ammoniation is performed by program-controlled heating under a mixed atmosphere, and then cooled to obtain a TiON heterogeneous carrier.

[0013] S5. Add a certain amount of TiON heterogeneous carrier into a three-necked flask containing deionized water, introduce inert gas, stir for a period of time, then slowly drop ruthenium chloride solution, react at room temperature for a period of time, then heat to a certain temperature for reaction, and after the reaction is completed, filter and wash to obtain a gray powder.

[0014] S6. The gray powder is transferred to a tube furnace, sintered in a hydrogen / argon mixed atmosphere, and cooled to obtain Ru@TiON.

[0015] S7. Add a certain mass of Ru@TiON catalyst to an organic solvent containing Nafion, ultrasonicate for a period of time to obtain catalyst ink, apply a certain amount of catalyst ink on the surface of the glassy carbon electrode, and dry to obtain a Ru-based catalyst electrode material.

[0016] Preferably, in S1, the mass of P25 is 200-2000 mg. The alkaline solution can be one of sodium hydroxide, potassium hydroxide and lithium hydroxide. The concentration of the alkaline solution is 5-15 mol / L, and the water used is one of deionized water and ultrapure water. The ultrasonic time is 10-60 min. The hydrothermal synthesis temperature is 150-240° C., and the reaction time is 18-54 h.

[0017] Preferably, in S2, the number of centrifugal washings is 3 to 6 times, and the solvent used is a mixed solvent of anhydrous ethanol and deionized water (volume ratio is 1:1 or 1:2). The acidic solution can be one or more combinations of nitric acid, boric acid, hydrochloric acid, sulfuric acid, and phosphoric acid, and the concentration of the acidic solution is 0.1 to 1 mol / L. The static time is 12 to 24 hours. The drying temperature is 60 to 80°C.

[0018] Preferably, in S3, the muffle furnace reaction temperature is 400-600° C., and the reaction time is 1-4 h.

[0019] Preferably, in S4, the content of the nano TiO2 rods is 150-350 mg. The mixed atmosphere is ammonia with any one of argon, helium and nitrogen, the atmosphere ratio is 1:1-5:1, and the gas flow rate is 50-200 sccm. The first stage heating rate is 5°C / min, the sintering temperature is 200-400°C, the second stage heating rate is 2°C / min, the sintering temperature time is 500-700°C, the third stage heating rate is 1°C / min, the sintering temperature time is 600-900°C, and the sintering time is 0.5-4h.

[0020] Preferably, in S5, the content of the TiON heterogeneous carrier is 50-150 mg, and the content of deionized water is 30-60 ml. The inert gas can be any one of nitrogen and argon. The stirring time is 30-60 min. The concentration of the ruthenium chloride solution is 0.3-1 mol / L, the drop volume is 5-30 ml, the room temperature reaction time is 3-6 h, the heating reaction time is 3-6 h, and the heating temperature is 50-100 ° C.

[0021] Preferably, in S6, the ratio of hydrogen to argon atmosphere is 5:95 or 10:90, the gas flow rate is 50-200 sccm, the heating rate is 5°C / min, the sintering temperature is 300-600°C, and the sintering time is 2-4h.

[0022] Preferably, in S7, the mass of the Ru@TiON catalyst is 2-4 mg, the volume of the Nafion solution is 10-40 μl, the organic solvent can be any one of isopropanol and ethanol. The ultrasonic time is 30-60 min. The amount of the catalyst ink added is 4-10 μl.

[0023] The present invention also relates to the use of the Ru-based catalyst of the alkaline fuel cell anode prepared by the preparation method as a hydrogen oxidation catalyst of the hydrogen fuel cell anode.

[0024] The advantages of the present invention are:

[0025] 1. The titanium oxynitride heterogeneous carrier obtained by the present invention through the four steps of "chemical reaction-critical growth-in-situ nucleation-high temperature reduction" has an obvious "dynamic electron flow" effect with Ru, which can adjust the electronic environment of Ru and change its H ad and OH ad adsorption mode, thereby achieving the catalyst's excellent mass activity and anti-oxidative deactivation ability.

[0026] 2. The prepared titanium oxynitride heterogeneous carrier has the advantages of both metal oxides and metal nitrides. Its high conductivity and oxygen affinity change the OH ad The adsorption mode makes OH adThe adsorption of Ru is transferred from Ru particles to the support surface, thus solving the competitive adsorption problem.

[0027] 3. The prepared Ru@TiON catalyst has excellent HOR kinetic activity, resistance to CO poisoning and stability.

[0028] 4. During the preparation process, the preparation process is simple and convenient, the conditions are mild, the preparation process is highly controllable, the reagents used are economical, and it is suitable for large-scale production.

[0029] In summary, the present invention simultaneously solves the two key problems of insufficient activity and easy oxidation deactivation of Ru-based catalysts, and provides a new idea for the rational design of Ru-based catalysts with high activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0031] Figure 1 This is a SEM image of the Ru@TiON-1 catalyst prepared in Example 1 of the present invention;

[0032] Figure 2 TEM image of the Ru@TiON-1 catalyst prepared in Example 1 of the present invention;

[0033] Figure 3 HRTEM image of the Ru@TiON-2 catalyst prepared in Example 2 of the present invention;

[0034] Figure 4 The HOR polarization curves of the Ru@TiON-3 catalyst and the Ru / C catalyst prepared in Example 3 of the present invention at 1600 rpm, and the electrolyte solution is 0.1 mol / L KOH solution. DETAILED DESCRIPTION

[0035] The present invention is described in detail below in conjunction with the examples and drawings. It should be understood that the following content is only used to illustrate the present invention and is not intended to limit the scope of the present invention. The raw materials required for the present invention can be purchased through commercial channels.

[0036] Example 1

[0037] 800mg P25 was dissolved in 100ml 12mol / L NaOH solution and ultrasonically stirred for 2h. Poured into a Teflon container and subjected to hydrothermal reaction at 220℃ for 24h. After the reaction was completed, it was washed three times with a mixed solvent of anhydrous ethanol and deionized water (volume ratio 1:1). The white precipitate obtained by centrifugation was poured into a 0.5mol / L hydrochloric acid solution and allowed to stand for 24h. Then filtered, washed and dried to obtain titanate nanofibers. The titanate nanofibers were then transferred to a muffle furnace, sintered at 400℃ for 2h, and nano-TiO2 rods were obtained after cooling. 300mg nano-TiO2 rods were transferred to a tubular furnace and sintered in a mixed atmosphere of ammonia / argon (1:1) with a gas flow rate of 100sccm. The first stage heating rate was 5℃ / min, the sintering temperature was 350℃, the second stage heating rate was 2℃ / min, the sintering temperature time was 500℃, the third stage heating rate was 1℃ / min, the sintering temperature time was 600℃, and the sintering time was 1h. Cooling to obtain TiON heterogeneous carrier. The obtained carrier was added to a three-necked flask containing 50ml of deionized water, introduced Ar, and stirred for 60min. 20ml of 0.5mol / L ruthenium chloride aqueous solution was added dropwise, stirred for 4h, then heated to 60℃, and continued to react for 4h. Filter and wash to obtain a gray catalyst precursor. 100mg of catalyst precursor powder was transferred to the middle of a tube furnace, and in a hydrogen / argon (5:95) atmosphere, the gas flow rate was 100sccm, and the temperature was increased to 600℃ at a rate of 5℃ / min, sintered for 2h, and cooled to room temperature to obtain Ru@TiON catalyst. Finally, the obtained catalyst was coated on a glassy carbon electrode for HOR performance testing.

[0038] Example 2

[0039] 800mg P25 was dissolved in 100ml 8mol / L NaOH solution and ultrasonically stirred for 2h. Poured into a Teflon container and subjected to hydrothermal reaction at 200℃ for 36h. After the reaction was completed, it was washed three times with a mixed solvent of anhydrous ethanol and deionized water (volume ratio 1:1). The white precipitate obtained by centrifugation was poured into a 0.5mol / L hydrochloric acid solution and allowed to stand for 24h. Then filtered, washed and dried to obtain titanate nanofibers. The titanate nanofibers were then transferred to a muffle furnace, sintered at 400℃ for 2h, and nano-TiO2 rods were obtained after cooling. 300mg nano-TiO2 rods were transferred to a tubular furnace and sintered in a mixed atmosphere of ammonia / argon (2:1) with a gas flow rate of 100sccm. The first stage heating rate was 5℃ / min, the sintering temperature was 350℃, the second stage heating rate was 2℃ / min, the sintering temperature time was 500℃, the third stage heating rate was 1℃ / min, the sintering temperature time was 600℃, and the sintering time was 2h. Cooling gave the TiON heterogeneous carrier. The obtained carrier was added to a three-necked flask containing 50ml of deionized water, introduced with Ar, and stirred for 60min. 20ml of 0.5mol / L ruthenium chloride aqueous solution was added dropwise, stirred for 4h, then heated to 60℃, and the reaction continued for 4h. Filter and wash to obtain the gray catalyst precursor. 100mg of the catalyst precursor powder was transferred to the middle of the tube furnace, and in a hydrogen / argon (5:95) atmosphere, the gas flow rate was 100sccm, and the temperature was raised to 600℃ at a rate of 5℃ / min, sintered for 2h, and the Ru@TiON-2 catalyst was obtained after cooling to room temperature. Finally, the obtained catalyst was coated on a glassy carbon electrode for HOR performance testing.

[0040] Example 3

[0041] 800mg P25 was dissolved in 100ml 10mol / L NaOH solution and ultrasonically stirred for 2h. Poured into a Teflon container and subjected to hydrothermal reaction at 200℃ for 48h. After the reaction was completed, it was washed three times with a mixed solvent of anhydrous ethanol and deionized water (volume ratio 1:1). The white precipitate obtained by centrifugation was poured into a 0.5mol / L hydrochloric acid solution and allowed to stand for 24h. Then filtered, washed and dried to obtain titanate nanofibers. The titanate nanofibers were then transferred to a muffle furnace, sintered at 400℃ for 2h, and nano-TiO2 rods were obtained after cooling. 300mg nano-TiO2 rods were transferred to a tubular furnace and sintered in a mixed atmosphere of ammonia / argon (2:1) with a gas flow rate of 100sccm. The first stage heating rate was 5℃ / min, the sintering temperature was 300℃, the second stage heating rate was 2℃ / min, the sintering temperature time was 500℃, the third stage heating rate was 1℃ / min, the sintering temperature time was 600℃, and the sintering time was 2h. Cooling gave the TiON heterogeneous carrier. The obtained carrier was added to a three-necked flask containing 50ml of deionized water, introduced with Ar, and stirred for 60min. 20ml of 0.5mol / L ruthenium chloride aqueous solution was added dropwise, stirred for 4h, then heated to 60℃, and the reaction continued for 4h. Filtering and washing gave the gray catalyst precursor. 100mg of the catalyst precursor powder was transferred to the middle of the tube furnace, and in a hydrogen / argon (10:90) atmosphere, the gas flow rate was 100sccm, the temperature was raised to 600℃ at a rate of 5℃ / min, sintered for 2h, and the Ru@TiON-3 catalyst was obtained after cooling to room temperature. Finally, the obtained catalyst was coated on a glassy carbon electrode for HOR performance testing.

[0042] The Ru@TiON-1 catalyst prepared in Example 1 of the present invention has a scanning electron microscope. Figure 1 As shown, its morphology is a uniform rod-like structure. The TEM image shows that the Ru nanoparticles prepared in this example are uniformly distributed on the heterogeneous carrier. Figure 3 This is a high-resolution transmission electron microscopy photo of Ru@TiON-2 obtained in Example 2. The Ru particles are evenly distributed on the surface of the carrier. The size of the Ru particles is in the range of 2-3nm. The lattice fringes of the carrier belong to TiN (200) (0.213nm) and TiO2 (101) (0.350nm). The lattice spacing of TiN and TiO2 has expanded and contracted respectively, resulting in an obvious heterogeneous interface. The formation of the heterogeneous interface in the surface Ru@TiON and the successful growth of Ru particles on the TiON heterogeneous carrier. Figure 4 This is the linear voltammetric scanning curve of the Ru@TiON-3 catalyst obtained in Example 3. It can be seen from the figure that the activity of the prepared catalyst is significantly improved, and at high potential, the activity of the material is not significantly reduced, indicating that the catalyst prepared by the present invention has excellent antioxidant ability.

[0043] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a Ru-based catalyst for an alkaline fuel cell anode, characterized in that A Ru-based electrocatalyst with "dynamic electron flow" effect was obtained by using the "chemical reaction-critical growth-in situ nucleation-high temperature reduction" process.

2. The method for preparing a Ru-based catalyst for an alkaline fuel cell anode according to claim 1, characterized in that The following steps are involved: S1. Titanate nanofibers were prepared by alkali-assisted hydrothermal method. P25 was used as a titanium source and added to an alkaline solution of a certain concentration. The solution was ultrasonically stirred for a period of time, and the mixed solution was added to a Teflon container for hydrothermal reaction to obtain a precipitate. S2. The precipitate of S1 is centrifugally washed until it becomes neutral, added into an acid solution of a certain concentration and allowed to stand for a period of time, and then filtered and dried to obtain titanate nanofibers. S3. The titanate nanofibers are transferred to a muffle furnace for high-temperature calcination to obtain nano-TiO2 rods. S4. A certain amount of nano-TiO2 rods are transferred to a tubular furnace, and ammoniation is performed by program-controlled heating under a mixed atmosphere, and then cooled to obtain a TiON heterogeneous carrier. S5. Add a certain amount of TiON heterogeneous carrier into a three-necked flask containing deionized water, introduce inert gas, stir for a period of time, then slowly drop ruthenium chloride solution, react at room temperature for a period of time, then heat to a certain temperature for reaction, and after the reaction is completed, filter and wash to obtain a gray powder. S6. The gray powder is transferred to a tube furnace, sintered in a hydrogen / argon mixed atmosphere, and cooled to obtain Ru@TiON. S7. Add a certain mass of Ru@TiON catalyst to an organic solvent containing Nafion, ultrasonicate for a period of time to obtain catalyst ink, apply a certain amount of catalyst ink on the surface of the glassy carbon electrode, and dry to obtain a Ru-based catalyst electrode material.

3. The method for preparing a Ru-based catalyst for an alkaline fuel cell anode according to claim 2, wherein in S1, the mass of P25 is 200-2000 mg. The alkaline solution can be one of sodium hydroxide, potassium hydroxide, and lithium hydroxide, or a combination of any two thereof. The concentration of the alkaline solution is 5-15 mol / L, and the water used is one of deionized water and ultrapure water. The ultrasonic time is 10-60 min.

4. The method for preparing a Ru-based catalyst for an alkaline fuel cell anode according to claim 2, wherein in S1, the hydrothermal synthesis temperature is 150 to 240°C and the reaction time is 18 to 54 hours.

5. The method for preparing a Ru-based catalyst for an alkaline fuel cell anode according to claim 2 is characterized in that in S2, the number of centrifugal washings is 3 to 6 times, and the solvent used is a mixed solvent of anhydrous ethanol and deionized water (volume ratio is 1:1 or 1:2).

6. The method for preparing a Ru-based catalyst for an alkaline fuel cell anode according to claim 2, wherein the acidic solution in S2 can be one or more of nitric acid, boric acid, hydrochloric acid, sulfuric acid, and phosphoric acid, and the concentration of the acidic solution is 0.1 to 1 mol / L. The standing time is 12 to 24 hours. The drying temperature is 60 to 80°C.

7. The method for preparing a Ru-based catalyst for an alkaline fuel cell anode according to claim 2, wherein in S3, the muffle furnace reaction temperature is 400-600°C, and the reaction time is 1-4 hours.

8. The method for preparing a Ru-based catalyst for an alkaline fuel cell anode according to claim 2, wherein the content of the nano-TiO2 rods in S4 is 150-350 mg. The mixed atmosphere is ammonia gas with any one of argon, nitrogen and helium, the atmosphere ratio is 1:1 to 5:1, and the gas flow rate is 50 to 200 sccm. The programmed temperature rise is a three-stage temperature rise process, the first stage has a temperature rise rate of 5°C / min, the sintering temperature is 200 to 400°C, the second stage has a temperature rise rate of 2°C / min, the sintering temperature time is 500 to 700°C, the third stage has a temperature rise rate of 1°C / min, the sintering temperature time is 600 to 900°C, and the sintering time is 0.5 to 4h.

9. The method for preparing a Ru-based catalyst for an alkaline fuel cell anode according to claim 2, wherein the content of the TiON heterogeneous carrier in S5 is 50-150 mg, and the content of deionized water is 30-60 ml. The inert gas can be any one of nitrogen and argon. The stirring time is 30-60 min. The concentration of the ruthenium chloride solution is 0.3-1 mol / L, the drop volume is 5-30 ml, the room temperature reaction time is 3-6 h, the heating reaction time is 3-6 h, and the heating temperature is 50-100 ° C.

10. The method for preparing a Ru-based catalyst for an alkaline fuel cell anode according to claim 2, wherein in S6, the ratio of hydrogen to argon atmosphere is 5:95 or 10:90, the gas flow rate is 50-200 sccm, the heating rate is 5°C / min, the sintering temperature is 300-600°C, and the sintering time is 2-4h.

11. The method for preparing a Ru-based catalyst for an alkaline fuel cell anode according to claim 2, wherein in S7, the mass of the Ru@TiON catalyst is 2-4 mg, the volume of the Nafion solution is 15-25 μl, the organic solvent can be any one of isopropanol and ethanol, the ultrasonic time is 30-60 min, and the amount of the catalyst ink added is 4-10 μl.

12. A Ru-based electrocatalyst prepared by the method according to any one of claims 1 to 11, characterized in that There is a "dynamic electron flow" effect between the active Ru clusters and the heterogeneous carriers.

13. Use of the Ru-based catalyst for alkaline fuel cell anode prepared by the preparation method according to any one of claims 1 to 12 as a hydrogen oxidation catalyst for hydrogen fuel cell anode.